Nutrition Education Through Storytelling Methods To Increase Consumption of Vegetables and Fruits For Elemntary School Children - Desi; Didik Hariyadi (POLTEKKES KEMENKES PONTIANAK, 2020)
Sufficient consumption of vegetables and fruits is one balanced nutritional indicator. Indonesian people (60.44%) consume fewer vegetables and fruits. The fiber content in vegetables and fruit is very useful for the body. Nutrition education in early childhood aims to shape nutritional behavior to be better. Efforts to improve nutrition knowledge can be done with appropriate, interesting, and easily understood media for children including storytelling methods. Therefore, it is necessary to research nutrition education through a storytelling method to increase the consumption of vegetables and fruits for elementary school children. This study aims to determine the effect of nutrition education through storytelling methods to increase the consumption of vegetables and fruits for elementary school children. This research is a pre-experiment. one group pre-post test. Data analysis in this study using the Paired Sample T-test. The subjects of this study were the elementary school children of 21 North Pontianak totaling 35 samples. The technique of collecting questionnaire data was chosen by direct interview, to see the difference in the consumption of vegetables and fruits. Based on the results of statistical tests of fruit intake scores before and after the intervention of 35 respondents obtained p-value 0,000 <0,05 this indicates that there is a significant difference between the fruit intake score before and after. The statistical test results of vegetable intake scores before and after the intervention were obtained p-value 0,000 <0,05, indicating that there were significant differences in vegetable intake scores in school children.